Merawat kepercayaan nasabah dengan memahami risiko kepatuhan di perbankan syariah: Studi literatur review - Sabita, Azmi (Maliki Interdisciplinary Journal, 2024)
This article aims to provide a comprehensive insight into how compliance risks can impact customer trust in Islamic banking, and to highlight specific steps that Islamic banking institutions can take to effectively manage these risks. Through a literature review methodology, the article identifies that compliance risks stem from non-compliance with legal regulations and Sharia principles, and can result in both direct and indirect losses. Additionally, the article outlines a risk management approach that can be adopted by Islamic banks, including the formation of specialized committees, risk identification, measurement, control, mitigation, and continuous evaluation of the applied strategies. With a focus on optimizing the role of the Dewan Pengawas Syariah (DPS), the article also emphasizes the importance of ensuring the alignment of Islamic banking products and systems with Sharia principles comprehensively. Consequently, through understanding and implementing effective compliance risk management, this article contributes to the sustainability and public trust in Islamic banking in Indonesia.